The Relationship between Knowledge and Parents' Attitudes towards the Importance of Breakfast for Children Aged 5-12 Years in the Village of Watutau, Lore Peore District: Hubungan Pengetahuan Dengan Sikap Orang Tua Tentang Pentingnya Sarapan Pagi Pada Anak Usia 5-12 Tahun Di Desa Watutau Kecamatan Lore Peore - Sisilia Megati; Ni Nyoman Udiani; Yulta kadang (Institute of Educational, Research, and Community Service, 2023)
This study aims to determine the